Coupled analysis of a 10 MW multi-body floating offshore wind turbine subjected to tendon failures. (October 2021) - Yang, Yang; Bashir, Musa; Michailides, Constantine; Mei, Xuan; Wang, Jin; Li, Chun
Abstract: In this study dynamic responses of a 10 MW offshore wind turbine supported by a multi-body floating platform that consists of a wide cylindrical platform and a cylindrical ballast body suspended by six tendons are analyzed and predicted for different tendon breakage scenarios. A newly-developed and validated fully coupled numerical tool (F2A) based on AQWA and FAST is used to perform aero-hydro-servo-elastic analysis of the floating offshore wind turbine (FOWT). The results indicate that the dynamic behavior of the platform is heavily influenced by the state of tendons health. Roll and yaw motions of the platform under a tendon breakage are found to experience 6 times magnitude amplification of the typical responses, depending on the specific environmental conditions considered. Moreover, the peak tension in the tendon adjacent to the broken tendon experienced an increase of 165% in magnitude. The collective-pitch mode of the platform and wave excitation that are the main contributors to the surge and pitch fluctuations are slightly affected by tendon breakages. The influence of tendon breakages is found to be only significant on the local-pitch and coupled-pitch modes of the platform. In addition, multifractal spectra of the platform accelerations under different tendon failure scenarios show distinct fractal characteristics that can effectively identify and diagnose tendon failures, which is essential to the development of a structural health monitoring system of FOWTs. Highlights: Coupled responses of a 10 MW floating wind turbine under damaged scenarios are investigated. Dynamic responses under intact and damaged tendon conditions are analyzed and predicted. Transient effects of tendon failures on the dynamic behavior are assessed. Multifractal spectrum analysis method is used to identify tendon damage features.